2009
DOI: 10.1002/ajhb.20908
|View full text |Cite
|
Sign up to set email alerts
|

A geometric morphometric approach to the quantification of population variation in sub‐Saharan African crania

Abstract: We report here on new data examining cranial variation in 18 modern human sub-Saharan African populations. Previously, we investigated variation within southern Africa; we now extend our analyses to include a series of Central, East, and West African crania, to further knowledge of the relationships between, and variation and regional morphological patterning in, those populations. The sample comprises 377 male individuals; the three-dimensional coordinates of 96 landmarks are analyzed using Procrustes-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Studied samples of the Serov race (Se_F and Se_H) from altitudes of 300-550 m were significantly larger in comparison to the other samples in centroid size of the skull and mandible. Geometric morphometrics gives a facility to evaluate the expression of allometric effects (O'Higgins & Collard, 2002;Cardini & Tongiorgi, 2003;Franklin et al, 2010). In our study, a negative significant correlation between RW1 and CS related to altitude was found in Serov race.…”
Section: Discussionsupporting
confidence: 54%
“…Studied samples of the Serov race (Se_F and Se_H) from altitudes of 300-550 m were significantly larger in comparison to the other samples in centroid size of the skull and mandible. Geometric morphometrics gives a facility to evaluate the expression of allometric effects (O'Higgins & Collard, 2002;Cardini & Tongiorgi, 2003;Franklin et al, 2010). In our study, a negative significant correlation between RW1 and CS related to altitude was found in Serov race.…”
Section: Discussionsupporting
confidence: 54%
“…Cranial morphology corroborates a Khoesan influence among some black subgroups, particularly the Xhosa and Zulu [19,66]. Furthermore, the myriad of laws associated with apartheid (e.g.…”
mentioning
confidence: 56%
“…Hit‐ratios from discriminant analyses of vervets were approximately 75–85% but only slightly larger than 50% when cross‐validated. This is only marginally better than the average 30–60% cross‐validated hit‐ratios from a study of cranial variation of sub‐Saharan populations of humans (Franklin, Cardini & Oxnard, 2010) and can be contrasted with much higher classification and cross validation rates within the guenons as a whole (Cardini & Elton, 2008a). Thus, on the basis of cranial morphology at least, the six most commonly recognized vervet taxa are better classed as subspecies rather than species.…”
Section: Discussionmentioning
confidence: 99%